Factors affecting accounting student's interest in pursuing careers at sharia financial institutions / Leny Nofianti ... [et al.] - Leny Nofianti; Febri Rahmi; Nurul Hafidah; Zattul (UiTM Cawangan Johor, 2020)
The research aims to investigate and analyse factors affecting accounting students' interest in pursuing careers at sharia financial institutions. In this research, we have modified previous research by adding independent variables. We examined religiosity factor, sharia accounting knowledge, intrinsic motivation, extrinsic motivation, third party influence, and career exposure. We also added gender as the control variable. Research sample consisted of all accounting students from either state or private universities in Riau. Taken by applying the purposive method sampling, the research sample was accounting students concentrated in sharia accounting in Riau. According to the field data, there were two universities having an accounting major with a sharia accounting concentration, i.e. Universitas Islam Negeri (UIN) Suska and Universitas Muhammadiyah Riau (UMRI). Meanwhile, students were allowed to take sharia accounting during 6th and 8th semesters. The number of samples that could be statistically processed was 235 people. Moreover, data were analysed by using SEM assisted by a statistic assistance tool WarpPls version 6.0. The findings argued that both intrinsic and extrinsic motivations became fundamental factors affecting students' interest in working at sharia financial institutions, and hence the hypothesis is accepted. Religiosity, sharia accounting knowledge, third party, career exposure, and gender did not give any significant effect to student's interest in pursuing careers in sharia financial institutions.